The proteasome inhibitor bortezomib reduced cholesterol accumulation in fibroblasts from Niemann–Pick type C patients carrying missense mutations. (21st August 2014) - Macías‐Vidal, Judit; Girós, Marisa; Guerrero, Martina; Gascón, Pere; Serratosa, Joan; Bachs, Oriol; Coll, Maria Josep
<x xml:space="preserve">Abstract</x> Niemann–Pick disease type C (NPC) is a lipid storage disorder mainly caused by mutations in the NPC1 gene. Approximately 60% of these mutations are missense changes that may induce reduced NPC1 protein levels by increased degradation via ubiquitin–proteasome. This is the case for the most prevalent worldwide mutation, p.Ile1061Thr, as well as for other three missense changes. In the present study, we analyzed the NPC1 levels in fibroblasts from eighteen NPC patients presenting missense mutations. We found that fourteen of these cells lines showed decreased levels of NPC1. Six of these cell lines were homozygous, whereas the other eight were associated with a frame shifting mutation. We focused our attention in the NPC homozygous samples and demonstrated that, in most of the cases, NPC1 reduction was a consequence of a decrease of its half‐life. NPC cells were treated not only with the proteasome inhibitors carbobenzoxy‐l‐leucyl‐l‐leucyl‐l‐leucinal or N‐acetyl‐leucyl‐leucyl‐norleucinal, both widely used as a research tools, but also with bortezomib, the first proteasome inhibitor to reach clinical applications, although it has never been used in NPC disease. We observed that, after treatment, the mutant NPC1 protein levels were partially recovered in most of the cell lines. Importantly, these mutant proteins partially recovered their activity and substantially reduced free cholesterol levels. These results suggest that by enhancing the NPC1 protein stability with the use of proteasome inhibitors, their functionality might be recovered and this might represent a therapeutical approach for future treatments of NPC disease resulting from specific missense mutations. Database Nucleotide and protein sequence data are available in the Genbank database under the accession numbers NM_000271.3 and NP_000262.1, respectively. Functional protein information is available in the UniProt protein database under the accession number O15118.